Turning from the Body as a Theological Matter to a Socio-cultural Approach to It A Study on Cultural History of Body in Iran” - Mohammad Amir Ahmadzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Socio-cultural reading is one of the most important approaches in cultural history, which is highlighted in the book "An Introduction to the Cultural History of the Body in Iran". In this article, the methodology and content of the text begin with the question of how the use of discourse approach in the cultural history of the body has an impact on the authors of the book and their reading of the sources and events of Iranian history and to find out its strengths and weaknesses. By using a critical approach and historical analysis, the discussion can be achieved in an attempt to formulate a new history of Iran, provide a different interpretation of the understanding of history, highlight the sociological approach and cultural studies of the body, interpret the cover as cultural, political and religious mentioned the use of literary and illustrated sources with the aim of strengthening the socio-cultural history approach. However, the universal and detailed view as a result of the dominance of the holistic and theory-based approach in the text of the work is impaired, and several historical data can be presented that challenge the inference of the authors of the book. On the other hand, the four divisions of the historical periods of Iran into the imperial era, the constitutional era, the modern era, and the religious era in different seasons have serious problems and do not correspond to the periods of Iranian history.